Titanium-loaded ferroresin and its preparation method and application

Through the in-situ synthesis method of ferrotitanium-loaded resin, anionic resin is used as a template carrier to form a ferrotitanium-loaded resin with a porous structure, which solves the problem of cadmium ion removal in the existing technology and achieves efficient and low-cost cadmium ion removal.

CN117816135BActive Publication Date: 2025-01-21JIANGSU HELPER FUNCTIONAL MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410215795.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-27
Publication Date
2025-01-21
Estimated Expiration
2044-02-27

AI Technical Summary

Technical Problem

The prior art has problems such as complex operation, high equipment and maintenance costs and cumbersome processes when dealing with cadmium ions in ternary lithium battery recycling liquid, making it difficult to achieve efficient and low-cost cadmium ions removal.

Method used

Titanium-loaded iron resin is used as a highly selective cadmium removal adsorbent, and anionic resin is used as a template carrier through in-situ synthesis to form a porous structure of titanium-iron-loaded resin, and its specific adsorption capacity is used to remove cadmium ions.

Benefits of technology

It achieves the efficient removal of cadmium ions in the ternary lithium battery recycling liquid. It has the advantages of green environmental protection, large specific surface area, low cost, good reusability, etc., and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117816135B_ABST
    Figure CN117816135B_ABST
Patent Text Reader

Abstract

The present invention relates to a titanium-loaded ferroresin and a preparation method and application thereof. The preparation method of the titanium-loaded ferroresin comprises the following steps: dissolving a titanium source and an iron source in a solvent to prepare a titanium-loaded ferroresin solution; mixing and reacting the titanium-loaded ferroresin solution and anionic resin to prepare a precursor solution; obtaining solid particles in the precursor solution, mixing and reacting with an alkali, and adjusting the pH of the solution; heating the reaction, and preparing the titanium-loaded ferroresin by a hydrothermal method. The method utilizes an in-situ synthesis method, uses anionic resin as a template carrier, forms a fixed bed treatment form, has a simple process, mild and controllable reaction conditions, and a high product purity. The obtained titanium-loaded ferroresin material nanoparticles are uniform in size, narrow in particle size distribution, and have a relatively regular pore structure. It is used as a cadmium removal adsorbent, has the characteristics of being green and environmentally friendly, large in specific surface area, strong in selective adsorption capacity, low in cost, good in reusability, and can be industrially produced, and can be applied to the removal of cadmium in ternary lithium battery recovery liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorbents, and in particular to a titanium-loaded ferroresin and a preparation method and application thereof. Background Art

[0002] The positive electrode material of ternary lithium battery is an ideal material for power lithium battery because of its wide source of raw materials, outstanding safety performance, good thermal stability and low cost. Under the concept of green development, the recycled liquid of lithium iron ion battery has important recycling value, but because it may contain heavy metal ions such as cadmium, nickel, cobalt and copper, it increases the difficulty of separation and purification. Among them, heavy metal cadmium (Cd) is a highly toxic heavy metal due to its strong mobility, high bioavailability and non-biodegradability. It is also a potential carcinogen for human organs such as lungs, kidneys and liver, which limits its recycling to a greater extent. Therefore, how to remove heavy metal cadmium ions in the recycled liquid has received widespread attention.

[0003] The traditional methods for treating cadmium ions in ternary lithium battery recovery liquid mainly include: precipitation method, membrane separation method, convection scanning electrochemical method and crystallization method. However, due to the disadvantages of the above technologies, such as complex operation, high equipment and maintenance costs, and cumbersome processes, it is difficult to apply them in practice. Therefore, providing a green, environmentally friendly, selectively adsorbent, and low-cost cadmium removal adsorbent is of great significance for improving the specific removal of cadmium content in ternary lithium battery recovery liquid. Summary of the invention

[0004] Based on this, the present invention provides a titanium-loaded ferroresin and a preparation method and application thereof. The titanium-loaded ferroresin can be used as a highly selective ternary lithium electrode cadmium removal adsorbent.

[0005] The technical solution is as follows:

[0006] A method for preparing titanium-loaded ferroresin comprises the following steps:

[0007] dissolving a titanium source and an iron source in a solvent to prepare a titanium-iron solution;

[0008] The titanium-iron solution and anion resin are mixed and reacted to prepare a precursor solution;

[0009] Obtaining solid particles in the precursor solution, mixing and reacting with a base, and adjusting the pH of the solution;

[0010] The temperature is raised to react, and the titanium-loaded ferroresin is prepared by a hydrothermal method.

[0011] In one embodiment, the iron source is selected from at least one of ferric chloride, ferric nitrate and ferric sulfate.

[0012] In one embodiment, the titanium source is selected from at least one of titanium tetrafluoride, tetraethyl titanate and tetrabutyl titanate.

[0013] In one embodiment, the solvent is selected from at least one of methanol, ethanol and ethylene glycol.

[0014] In one of the embodiments, in the titanium-iron solution, the concentration of iron ions is 0.5 mol / L to 5 mol / L.

[0015] In one of the embodiments, in the titanium-ferro solution, the concentration of titanium ions is 1 mol / L to 10 mol / L.

[0016] In one embodiment, the anion resin is selected from at least one of styrene anion resin, acrylic anion resin and quaternary ammonium anion resin.

[0017] In one embodiment, the particle size of the anion resin is 180 μm to 300 μm.

[0018] In one embodiment, the mass ratio of the anion resin to the titanium source and the iron source is (0.7-1.2):(1-3):1.

[0019] In one embodiment, in the step of preparing the precursor solution, the reaction temperature is 80° C. to 120° C., and the reaction time is 12 h to 16 h.

[0020] In one embodiment, the base is selected from at least one of sodium hydroxide, potassium hydroxide and ammonia water.

[0021] In one embodiment, in the step of preparing titanium-loaded ferro-resin parameters by hydrothermal method, the pH value is 2-6.

[0022] In one of the embodiments, the mass ratio of the alkali to the solid particles is (1-1.4):13.

[0023] In one of the embodiments, in the step of preparing the titanium-loaded ferroresin by a hydrothermal method, the reaction temperature is 80° C. to 120° C., and the reaction time is 12 h to 16 h.

[0024] In one embodiment, after the step of preparing the titanium-loaded ferroresin by a hydrothermal method, the titanium-loaded ferroresin is further purified.

[0025] In one embodiment, the purification process of the titanium-loaded ferroresin comprises the following steps:

[0026] The titanium-loaded ferroresin is subjected to water washing and alcohol washing treatment.

[0027] In one embodiment, the alcohol used in the alcohol washing is selected from at least one of methanol, ethanol and ethylene glycol.

[0028] The present invention also provides a titanium-loaded ferroresin, which is prepared according to the preparation method of the titanium-loaded ferroresin as described above.

[0029] In one embodiment, the titanium-containing ferroresin has a porous structure with a porosity of 60% to 70%.

[0030] In one embodiment, the titanium-iron resin has a porous structure, and the diameter of a single pore is 10 nm to 1000 nm.

[0031] In one of the embodiments, in the titanium-iron resin, the particle size of the titanium-iron nanomaterial is 180nm to 280nm.

[0032] The present invention also provides an adsorbent, comprising the titanium-loaded ferroresin as described above.

[0033] In one embodiment, the adsorbent is used for ternary lithium electrode wet method to remove cadmium.

[0034] The present invention has at least the following beneficial effects:

[0035] The preparation method of the titanium-loaded ferroresin provided by the present invention utilizes an in-situ synthesis method, uses an anion resin as a template carrier, forms a fixed bed treatment form, has a simple process, mild and controllable reaction conditions, and a high product purity. The prepared titanium-loaded ferroresin material nanoparticles have uniform size, narrow particle size distribution, and a relatively regular pore arrangement structure. It is used as a cadmium removal adsorbent, has the characteristics of being green and environmentally friendly, having a large specific surface area, having specific adsorption capacity, low cost, good reusability, and being industrially producible, and can be applied to the removal of cadmium in ternary lithium battery recovery liquid.

[0036] After testing, the titanium-loaded ferro-resin prepared by the present invention is used as a cadmium removal adsorbent, and the solution contains polymetallic ions (Cu 2+ 、Cd 2+ 、Co 2+ , Mn 4+ and Li + ) in the presence of, the titanium-supported ferroresin adsorption material of the present invention can adsorb a large amount of Cd 2+ , while for Cu 2+ 、Co 2+ , Mn 4+ and Li + The adsorption is poor, which shows that the iron-loaded resin of the present invention has high efficiency and selective adsorption of Cd 2+The adsorption capacity in 20 hours is 37 g / L and the adsorption equilibrium capacity is 49 g / L, which fully reflects its advantages of short adsorption time, high selective adsorption, large adsorption capacity and good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a physical picture of the material prepared in Example 1;

[0038] Figure 2 is a SEM image of the resin material in this embodiment 1;

[0039] Figure 3 is the XRD pattern of the material prepared in this Example 1;

[0040] Figure 4 is the pore size distribution diagram of the ion exchange resin in this Example 1;

[0041] Figure 5 This is a curve chart showing the change of the adsorption capacity Q of the cadmium removal adsorbent in Example 1 over time. DETAILED DESCRIPTION

[0042] The present invention will be further described in detail below in conjunction with specific embodiments and accompanying drawings. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0044] Where “including,” “having,” and “comprising” are used herein, it is intended to cover a non-exclusive inclusion, and another component may also be added unless explicit limiting terms such as “only,” “consisting of,” etc. are used.

[0045] The words "preferably", "more preferably", "preferably", "better", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the statement of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention. That is, in the present invention, "preferably", "more preferably", "preferably", "better", etc. are only used to describe implementation methods or examples with better effects, but do not constitute a limitation on the scope of protection of the present invention.

[0046] In the present invention, “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.

[0047] In the present invention, "at least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multilayer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present invention, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0048] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0049] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0050] In the present invention, "above" or "below" includes the number itself. For example, "below 1" includes 1.

[0051] The temperature parameters in the present invention, if not specifically limited, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0052] Unless mentioned to the contrary, terms in the singular may include plural forms and should not be construed as being one in number.

[0053] The raw materials, reagents and materials used in the following specific embodiments are all commercially available products unless otherwise specified.

[0054] The traditional methods for treating cadmium ions in ternary lithium battery recovery liquid mainly include: precipitation method, membrane separation method, convection scanning electrochemical method and crystallization method, but the above technologies have disadvantages that cannot be ignored, such as complex operation, high equipment and maintenance costs, and cumbersome processes, and are difficult to apply in practice. Therefore, how to comprehensively improve the above problems existing in the prior art and obtain a green, environmentally friendly, selectively adsorbent, and low-cost cadmium removal adsorbent is of great significance for improving the specific removal of cadmium content in ternary lithium battery recovery liquid.

[0055] Based on this, the present invention provides a titanium-loaded iron resin and a preparation method thereof. The iron-loaded iron resin can be used as a highly selective ternary lithium electrode cadmium removal adsorbent.

[0056] The technical solution is as follows:

[0057] A method for preparing titanium-loaded ferroresin comprises the following steps:

[0058] dissolving a titanium source and an iron source in a solvent to prepare a titanium-iron solution;

[0059] Mixing the titanium-iron solution and anionic resin to prepare a precursor solution;

[0060] Obtaining solid particles in the precursor solution, mixing and reacting with a base, and adjusting the pH of the solution;

[0061] The temperature is raised to react, and the titanium-loaded ferroresin is prepared by a hydrothermal method.

[0062] The anionic resin used as the template carrier mainly contains strong reactive groups, such as -N (CH 3 ) 3 + , in the hydroxyl form, -N (CH 3 ) 3 + The hydroxide ions in OH- can be quickly released for exchange. In addition, it also contains strong basic groups, such as quaternary ammonium groups (also known as quaternary amine groups) -NR 3 OH (R is a hydrocarbon group), which can dissociate into OH in water - It is strongly alkaline, and when the negatively charged groups of the resin can adsorb and combine with the cations in the solution, an anion exchange reaction is generated, which is stable and efficient, and is therefore widely used in many fields such as biomaterial production, pharmaceutical product development, and wastewater treatment. At the same time, this resin has strong dissociation and can work normally at different pH levels. It can be regenerated with strong alkali (such as NaOH), and is a green, environmentally friendly, and low-cost carrier material.

[0063] The preparation method of the titanium-loaded ferroresin provided by the present invention utilizes an in-situ synthesis method, uses an anion resin as a template carrier, forms a fixed bed treatment form, has a simple process, mild and controllable reaction conditions, high product purity, and the prepared ferroresin material nanoparticles are uniform in size, narrow in particle size, and have a relatively regular pore arrangement structure. If the titanium-loaded ferroresin is used as a cadmium removal adsorbent, it has the characteristics of being green and environmentally friendly, having a large specific surface area, having a specific adsorption capacity, low cost, good reusability, and being industrially producible, and can be applied to the removal of cadmium in ternary lithium battery recovery liquid.

[0064] The preparation method of the titanium-loaded ferroresin material of the present invention is described in detail below in a step-by-step manner.

[0065] S100: dissolving a titanium source and an iron source in a solvent to prepare a titanium-iron solution.

[0066] In one embodiment, the iron source is selected from at least one of ferric chloride, ferric nitrate and ferric sulfate.

[0067] In one embodiment, the titanium source is selected from at least one of titanium tetrafluoride, tetraethyl titanate and tetrabutyl titanate.

[0068] In one embodiment, the solvent is selected from at least one of methanol, ethanol and ethylene glycol.

[0069] In one embodiment, in the titanium-iron solution, the concentration of iron ions is 0.5 mol / L to 5 mol / L, including but not limited to 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L.

[0070] In one embodiment, in the titanium-iron solution, the concentration of titanium ions is 1 mol / L to 10 mol / L, including but not limited to 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L.

[0071] In one embodiment, a titanium source and an iron source are dissolved in a solvent at room temperature, such as 25±15° C., to prepare a titanium-iron solution.

[0072] S200: mixing the titanium-iron solution and anion resin to react to prepare a precursor solution.

[0073] In one embodiment, the anion resin is selected from at least one of styrene anion resin, acrylic anion resin and quaternary ammonium anion resin.

[0074] In one embodiment, the particle size of the anion resin is 180 μm to 300 μm, including but not limited to 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 250 μm, 280 μm, 290 μm or 300 μm.

[0075] In one embodiment, the mass ratio of the anion resin to the titanium source and the iron source is (0.7-1.2):(1-3):1, including but not limited to 0.7:1:1, 0.8:1:1, 0.9:1:1, 1.0:1:1, 1.1:1:1, 1.2:1:1, 0.7:2:1, 0.8:2:1, 0.9:2:1, 1.0:2:1, 1.1:2:1, 1.2:2:1, 0.7:3:1, 0.8:3:1, 0.9:3:1, 1.0:3:1, 1.1:3:1 or 1.2:3:1.

[0076] In one embodiment, in the step of preparing the precursor solution, the reaction temperature is 80°C to 120°C, including but not limited to 80°C, 90°C, 100°C, 110°C or 120°C.

[0077] In one embodiment, in the step of preparing the precursor solution, the reaction time is 12 h to 16 h, including but not limited to 12 h, 13 h, 14 h, 15 h or 16 h.

[0078] In one embodiment, the titanium-iron solution and the anion resin are mixed to prepare a precursor solution, comprising the following steps:

[0079] Slowly add 10g to 100g of dry anion resin to the titanium-containing iron solution obtained in S100, and react at 80°C to 120°C for 12h to 16h. It can be understood that the temperature for preparing the precursor solution includes but is not limited to 80°C, 90°C, 100°C, 110°C or 120°C; the time for preparing the precursor solution includes but is not limited to 12h, 13h, 14h, 15h or 16h.

[0080] S300: obtaining solid particles of the precursor solution, mixing and reacting with a base, and adjusting the pH of the solution.

[0081] In one embodiment, the base is selected from at least one of sodium hydroxide, potassium hydroxide and ammonia water.

[0082] In one embodiment, the mass ratio of the alkali to the solid particles is (1-1.4):13, including but not limited to 1:13, 1.1:13, 1.2:13, 1.3:13 or 1.4:13.

[0083] In one embodiment, the pH is 2-6.

[0084] S400: heating the reaction to prepare the titanium-iron resin by a hydrothermal method. As the reaction proceeds, titanium-iron double-layer hydroxide is gradually formed in the pores of the anion resin.

[0085] In one embodiment, in the step of preparing the titanium-loaded ferroresin by a hydrothermal method, the reaction temperature is 80°C to 120°C, including but not limited to 80°C, 90°C, 100°C, 110°C or 120°C.

[0086] In one embodiment, in the step of preparing the titanium-loaded ferroresin by a hydrothermal method, the reaction time is 12 hours to 16 hours, including but not limited to 12 hours, 13 hours, 14 hours, 15 hours or 16 hours.

[0087] S500: purifying the titanium ferroresin.

[0088] In one embodiment, the purification process of the titanium ferroresin comprises the following steps:

[0089] The titanium ferroresin is subjected to water washing and alcohol washing treatment.

[0090] In one embodiment, the alcohol used in the alcohol washing is selected from at least one of methanol, ethanol and ethylene glycol.

[0091] It can be understood that the end point of water washing is when the pH of the aqueous solution is close to neutral, that is, the pH of the aqueous solution is 7.0-7.5.

[0092] The present invention also provides a titanium-loaded ferroresin, characterized in that it is prepared according to the preparation method of the ferroresin as described above. Further, the titanium-loaded ferroresin material is yellow-brown nanoparticles with uniform particle size, and in the titanium-loaded ferroresin, the particle size of the titanium-loaded ferroresin nanomaterial is 180nm to 280nm, and the particle size distribution is narrow. Furthermore, the titanium-loaded ferroresin material has a relatively regular pore structure / porous structure, a porosity of 60% to 70%, and a single pore diameter of 10nm to 1000nm.

[0093] The present invention also provides an adsorbent, comprising the titanium-loaded ferroresin as described above.

[0094] In one embodiment, the adsorbent is used for wet cadmium removal from ternary lithium batteries.

[0095] In one embodiment, the wet cadmium removal comprises the following steps:

[0096] 10 mL of the above-mentioned titanium-iron resin was loaded into a glass chromatography column, and 10 BV of ternary lithium battery wastewater solution was added at a flow rate of 2 BV / h. 1 wt% HCl was used for desorption. The desorption temperature was 40 °C and the desorption flow rate was 1 BV / h.

[0097] The following is further described in conjunction with specific embodiments and comparative examples.

[0098] Example 1

[0099] This embodiment provides a titanium-loaded ferro-resin and a preparation method thereof, which are specifically as follows:

[0100] (1) Weigh 24.8 g of analytically pure titanium tetrafluoride and 16.2 g of ferric chloride, add 100 ml of ethanol, and stir at room temperature for 60 min to obtain a uniform mixed solution.

[0101] (2) Add 25 g of washed and dried polystyrene macroporous anion resin (average pore size 240 nm) to the mixed solution obtained in step (1), and stir for 4 hours.

[0102] (3) The mixed solution in step (2) was introduced into a 250 ml Teflon reactor, 2 g NaOH was added, the pH was adjusted to 6, the reaction temperature was set to 80 °C, the heating rate was set to 6 °C / min, and the reaction time was set to 12 h.

[0103] (4) After the reaction is completed, the reactor is placed in a refrigerator to cool for 1 hour, then washed three times with pure water and ethanol respectively, and dried to obtain the desired titanium-loaded ferroresin sample, which is recorded as product A.

[0104] Example 2

[0105] This embodiment provides a titanium-loaded ferro-resin and a preparation method thereof, which are specifically as follows:

[0106] (1) Weigh 24.8 g of analytically pure titanium tetrafluoride and 16.2 g of ferric chloride, add 100 ml of ethanol, and stir at room temperature for 60 min to obtain a uniform mixed solution.

[0107] (2) Add 25 g of washed and dried polystyrene macroporous anion resin (average pore size 240 nm) to the mixed solution obtained in step (1), and stir for 4 hours.

[0108] (3) The mixed solution in step (2) was introduced into a 250 ml Teflon reactor, 2 g NaOH was added, the pH was adjusted to 6, the reaction temperature was set to 120 °C, the heating rate was set to 6 °C / min, and the reaction time was set to 12 h.

[0109] (4) After the reaction is completed, the reactor is placed in a refrigerator to cool for 1 hour, then washed three times with pure water and ethanol respectively, and dried to obtain the desired titanium-loaded ferroresin sample, which is recorded as product B.

[0110] Example 3

[0111] This embodiment provides a titanium-loaded ferro-resin and a preparation method thereof, which are specifically as follows:

[0112] (1) Weigh 24.8 g of analytically pure titanium tetrafluoride and 16.2 g of ferric chloride, add 100 ml of ethanol, and stir at room temperature for 60 min to obtain a uniform mixed solution.

[0113] (2) Add 25 g of washed and dried polystyrene macroporous anion resin (average pore size 240 nm) to the mixed solution obtained in step (1), and stir for 4 hours.

[0114] (3) The mixed solution in step (2) was introduced into a 250 ml Teflon reactor, 2 g NaOH was added, the pH was adjusted to 6, the reaction temperature was set to 120 °C, the heating rate was set to 6 °C / min, and the reaction time was set to 16 h.

[0115] (4) After the reaction is completed, the reactor is placed in a refrigerator to cool for 1 hour, then washed three times with pure water and ethanol respectively, and dried to obtain the desired titanium-loaded ferroresin sample, which is recorded as product C.

[0116] Example 4

[0117] This embodiment provides a titanium-loaded ferro-resin and a preparation method thereof, which are specifically as follows:

[0118] (1) Weigh 37.2 g of analytically pure titanium tetrafluoride and 16.2 g of ferric chloride, add 100 ml of ethanol, and stir at room temperature for 60 min to obtain a uniform mixed solution.

[0119] (2) Add 25 g of washed and dried polystyrene macroporous anion resin (average pore size 240 nm) to the mixed solution obtained in step (1), and stir for 4 hours.

[0120] (3) The mixed solution in step (2) was introduced into a 250 ml Teflon reactor, 2 g NaOH was added, the pH was adjusted to 6, the reaction temperature was set to 120 °C, the heating rate was set to 6 °C / min, and the reaction time was set to 12 h.

[0121] (4) After the reaction is completed, the reactor is placed in a refrigerator to cool for 1 hour, then washed three times with pure water and ethanol respectively, and dried to obtain the desired titanium-loaded ferroresin sample, which is recorded as product D.

[0122] Comparative Example 1

[0123] This comparative example provides an iron-loaded resin and a preparation method thereof, which are specifically as follows:

[0124] (1) Weigh 16.2 g of analytically pure ferric chloride, add 100 ml of ethanol, and stir at room temperature for 60 min to obtain a uniform mixed solution.

[0125] (2) Add 25 g of washed and dried polystyrene macroporous anion resin (average pore size 240 nm) to the mixed solution obtained in step (1), and stir for 4 hours.

[0126] Take 100 ml of the iron-loaded resin particles obtained in step (2), add 100 ml of 25 wt% NaOH alkaline solution, and continue stirring at 150°C for 24 hours. After the reaction is completed, wash three times with pure water and store for later use.

[0127] (3) The mixed solution in step (2) was introduced into a 250 ml Teflon reactor, 2 g NaOH was added, the pH was adjusted to 6, the reaction temperature was set to 120 °C, the heating rate was set to 6 °C / min, and the reaction time was set to 12 h.

[0128] (4) After the reaction is completed, the reactor is placed in a refrigerator to cool for 1 hour, then washed three times with pure water and ethanol respectively, and dried to obtain the desired iron-loaded resin sample, which is recorded as product E.

[0129] The performance test of the products obtained in Examples 1 to 4 and Comparative Example 1 was carried out as follows:

[0130] Configuration containing Cd 2+ , Cu 2+ 、Co 2+ , Mn 2+ and Li + The iron-containing waste liquid of five metal ions has a content of 100 ppm for each metal ion; 10 mL of the iron-containing waste liquid is placed in a conical flask, and 10 g of the products of Examples to Example 4 and Comparative Example 1 are added respectively, and the conical flask is placed in a constant temperature oscillator for 6 hours for adsorption treatment; filtration treatment is performed using a 0.45 μm microfiltration membrane, and then the content of each metal ion in the iron-containing waste liquid after adsorption treatment is determined by the ICP method, and the results are shown in Table 1.

[0131] Table 1 Comparison of ternary lithium battery solution containing cadmium before and after adsorption

[0132]

[0133] As shown in Table 1, in the presence of polymetallic ions in the solution, the iron-loaded resin adsorption material synthesized according to the method shown in the embodiment of the present invention can efficiently and selectively adsorb Cd2+ , and has excellent adsorption performance, and is suitable for the selective adsorption and separation of cadmium in complex multi-heavy metal ion environments.

[0134] Figure 1 This is a physical picture of the material prepared in Example 1 of the present invention, which can be seen to be a yellow-brown solid.

[0135] Figure 2 This is a SEM image of the resin material in Example 1 of the present invention. It can be seen that it has a lamellar structure, and further, it can be observed that it has a porous structure.

[0136] Figure 3 This is the XRD diagram of the material prepared in Example 1 of the present invention, indicating that the titanium-iron double-layer hydroxide was successfully synthesized.

[0137] Figure 4 is the pore size distribution diagram of the titanium-containing ferroresin in Example 1 of the present invention, Figure 4 It can be seen that the pore size of the titanium-loaded ferroresin material prepared in Example 1 is mainly concentrated in the range of 220 nm to 240 nm, and the particle size distribution is narrow.

[0138] Application examples:

[0139] The titanium-containing ferro-resin in Example 1 of the present invention is used as a cadmium removal adsorbent, and the specific steps are as follows:

[0140] 10 mL of the above-mentioned titanium-iron resin was loaded into a glass chromatography column, and 10 BV of ternary lithium battery wastewater solution was added at a flow rate of 2 BV / h. 1 wt% HCl was used for desorption. The desorption temperature was 40 °C and the desorption flow rate was 1 BV / h.

[0141] Figure 5 The graph of the adsorption capacity Q of the titanium-containing ferro-resin as a cadmium removal adsorbent over time in Example 1 of the present invention is shown in FIG. Figure 5 It can be seen that the cadmium removal material prepared in Example 1 of the present invention has excellent cadmium removal performance.

[0142] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0143] The above-described embodiments only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in detail, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present invention, several modifications and improvements can be made, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by ordinary technicians in this field through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description and drawings can be used to explain the contents of the claims.

Claims

1. A method for preparing titanium-loaded ferroresin, characterized in that: The steps include: dissolving a titanium source and an iron source in a solvent to prepare a titanium-iron solution; The titanium-iron solution and anion resin are mixed and reacted to prepare a precursor solution; Obtaining solid particles in the precursor solution, mixing and reacting with a base, and adjusting the pH of the solution; The temperature is raised to react, and the titanium-iron resin is prepared by a hydrothermal method; as the reaction proceeds, titanium-iron double-layer hydroxide is gradually formed in the pores of the anion resin; The iron source is selected from at least one of ferric chloride, ferric nitrate and ferric sulfate.

2. The method for preparing titanium-loaded ferroresin according to claim 1, characterized in that: In the step of preparing the titanium-loaded ferroresin by a hydrothermal method, the reaction temperature is 80° C. to 120° C., and the reaction time is 12 h to 16 h.

3. The method for preparing titanium-loaded ferroresin according to claim 1, characterized in that: Satisfy at least one of the following (1) to (4): (1) The titanium source is selected from at least one of titanium tetrafluoride, tetraethyl titanate and tetrabutyl titanate; (2) the solvent is selected from at least one of methanol, ethanol and ethylene glycol; (3) In the titanium-iron solution, the concentration of iron ions is 0.5 mol / L to 5 mol / L; (4) In the titanium-iron solution, the concentration of titanium ions is 1 mol / L to 10 mol / L.

4. The method for preparing titanium-loaded ferroresin according to claim 1, characterized in that: Satisfy at least one of the following (1) to (2): (1) The anion resin is selected from at least one of a styrene anion resin, an acrylic anion resin and a quaternary ammonium anion resin; (2) The particle size of the anion resin is 180 μm to 300 μm.

5. The method for preparing the titanium-loaded ferroresin according to any one of claims 1 to 4, characterized in that: The parameters for preparing the precursor solution include at least one of the following (1) to (2): (1) The mass ratio of the anion resin to the titanium source to the iron source is (0.7-1.2):(1-3):1; (2) The reaction temperature is 80°C to 120°C, and the reaction time is 12h to 16h.

6. The method for preparing the titanium-loaded ferroresin according to any one of claims 1 to 4, characterized in that: Satisfy at least one of the following (1) to (3): (1) The alkali is selected from at least one of sodium hydroxide, potassium hydroxide and ammonia water; (2) The mass ratio of the alkali to the solid particles is (1-1.4):13; (3) pH is 2 to 6.

7. The method for preparing the titanium-loaded ferroresin according to any one of claims 1 to 4, characterized in that: After the hydrothermal method, the titanium-loaded ferroresin is further subjected to water washing and alcohol washing treatment.

8. A titanium-loaded ferroresin, characterized in that: The method for preparing the titanium-loaded ferroresin according to any one of claims 1 to 7 is adopted.

9. The titanium-loaded ferroresin according to claim 8, characterized in that: Satisfy at least one of the following (1) to (3): (1) The titanium-containing ferro-resin has a porous structure with a porosity of 60% to 70%; (2) In the titanium-iron-loaded resin, the pore size of a single pore is 10 nm to 1000 nm; (3) In the titanium-iron resin, the particle size of the titanium-iron nanomaterial is 180nm to 280nm.

10. An adsorbent, characterized in that: The invention comprises the titanium-loaded ferroresin as claimed in claim 8 or 9.

11. The adsorbent according to claim 10, characterized in that The adsorbent is used for removing cadmium by ternary lithium electrode wet method.

Citation Information

Patent Citations

  • Nano-hydroxyferric oxide modified anion resin composite material and preparation method and application thereof

    CN109967134A